DIFFERENT MODES OF TURBULENCE IN THE ACTIVE REGIONS OF THE SOLAR PHOTOSPHERE - Kozak, L. V.; Kostyk, R. I.; Cheremnykh, O. K. (Одеські астрономічні публікації, 2013)
In work the range of different methods for the analysis of characteristics of turbulent processes in the active regions of the solar photosphere has been used. The changes of fluctuations distribution function and its moments were analyzed, spectral analysis was carried out. It was found out from the observations of active region carried out with the 70-cm vacuum tower telescope VTT in Isanie (Tenerife Island,Spain) that the turbulent processes in the sun photosphere are characterized by two different spectra of turbulence. The first one of them is well known Kolmohorov spectrum, which describes the plasma with zero mean magnetic field. The second one is the Kraichnan spectrum with a different from zero mean magnetic field. Transition from one spectrum type to another one occurs at scale of3 Mm. We have to note that the scale3 Mmcorresponds to one of mesogranulation and testifies about non-zero mean magnetic fields for the consideration of regions exceeding the granulation in active regions of the photosphere. Besides, this clears the possibility of appearance of selforganizing magnetic plasma structures such as spots, active regions and complexes of activity.